2014
DOI: 10.14411/eje.2014.066
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal characteristics and evolutionary relationships of the Palearctic black fly Simulium carthusiense (Diptera: Simuliidae)

Abstract: Abstract. The giant, polytene chromosomes of Simulium carthusiense Grenier & Dorier, 1959 were mapped, and all rearrangements were resolved relative to the standard banding sequence for the S. vernum group. The species is chromosomally cohesive from Austria to Spain, and is characterized by a chromocenter, two unique fixed inversions, 10 unique autosomal polymorphisms, and undifferentiated sex chromosomes. Rare individuals (3%) have two types of supernumerary chromosomes, representing the third example of a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…bees, wasps, mosquitoes, spiders), all entomological studies carried out during the outbreaks in 2011 and 2012 demonstrated that the aforementioned biting increment was due to the abundance of blackflies at the Ebro riverbanks of the city of Zaragoza [4, 5]. Of the 55 species known from Spain [6, 7], S. erythrocephalum is assumed to cause the majority nuisance of problems in the country because its immature stages are commonly found together with non-human biting species (subgenus Wilhelmia ) in rivers near the areas of nuisance reports [4]. The current study is the first to use the human-landing-collection (HLC) technique for collecting blackflies in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…bees, wasps, mosquitoes, spiders), all entomological studies carried out during the outbreaks in 2011 and 2012 demonstrated that the aforementioned biting increment was due to the abundance of blackflies at the Ebro riverbanks of the city of Zaragoza [4, 5]. Of the 55 species known from Spain [6, 7], S. erythrocephalum is assumed to cause the majority nuisance of problems in the country because its immature stages are commonly found together with non-human biting species (subgenus Wilhelmia ) in rivers near the areas of nuisance reports [4]. The current study is the first to use the human-landing-collection (HLC) technique for collecting blackflies in Spain.…”
Section: Introductionmentioning
confidence: 99%